Anesthesia Management of Cesarean Section in Women with Peripartum Cardiomyopathy: A Case Series - Praskita Pande; Ruddi Hartono (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Peripartum cardiomyopathy (PPCM) is a rare but serious heart condition that occurs during late pregnancy or within the first few months after delivery. It can lead to significant maternal and fetal morbidity and mortality. Anesthetic management of PPCM patients undergoing cesarean section (C-section) is challenging due to the hemodynamic instability and potential for complications. Case presentation: This case series describes the anesthetic management of four women with PPCM undergoing C-section. Various anesthetic techniques were employed, including combined spinal-epidural (CSE) and epidural anesthesia, with careful monitoring and individualized management strategies. Case 1 present a 34-year-old female with mild mitral regurgitation, mild tricuspid regurgitation, mild pulmonary regurgitation, intermediate probability pulmonary hypertension, hypertensive heart failure, and obesity underwent C-section under CSE anesthesia with ropivacaine and bupivacaine. Case 2 present a 26-year-old female with PPCM and mild mitral regurgitation underwent C-section under CSE anesthesia with ropivacaine and bupivacaine. Case 3 present a 26-year-old female with PPCM, thrombocytosis, and hypoalbuminemia underwent C-section under epidural anesthesia with ropivacaine and fentanyl. Case 4 present a 30-year-old female with PPCM, marginal placenta previa, uterine myoma, and severe myopia underwent C-section under epidural anesthesia with ropivacaine and fentanyl. Conclusion: Regional anesthesia, particularly CSE and epidural techniques, appears to be a safe and effective anesthetic approach for C-sections in women with PPCM. Meticulous hemodynamic monitoring and individualized management are crucial for successful outcomes.